Organizational Mail Tracking With Security Using 3d Password And Database Encryption (International Journal of Engineering and Computer Science, 2018)
This paper proposes to design an organizational mail server which has the property of tracking unauthorized mails send between employees of different scales in an organization for reducing security issues. It is a direct intruding into each employee’s mail in an organization, tracking and monitoring the mail, which is done in a secret format. In Mail Compose web page, an additional function which does not allow employees to send invalid mail and send a report to the administrator about this attempt. Administrator stores these reports in a separate database in an encrypted format. For secure operations, 3D Password is used as the protection tool for administrator login.